2015
DOI: 10.3748/wjg.v21.i2.525
|View full text |Cite
|
Sign up to set email alerts
|

Patient age and duration of colonoscopy are predictors for adenoma detection in both proximal and distal colon

Abstract: Increasing age and longer duration of colonoscopy are factors with a strong impact on adenoma detection both in the proximal and distal colon. Since proximal adenomas occurred in absence of distal adenomas, complete colonoscopy should be performed for screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
5
0
2
Order By: Relevance
“…Data from a large Korean cohort have shown that especially over and above the 4th decade of life, the ADR reaches 28% as compared to the 2nd decade of life when it is only 14% [7]. Comparable results were published in a large European register [8,9]. Data from the United States [10] endorse European and Asian experiences and stress the importance of raising ADR in patients above 50 years of age.…”
Section: Factors Influencing the Adrsupporting
confidence: 48%
“…Data from a large Korean cohort have shown that especially over and above the 4th decade of life, the ADR reaches 28% as compared to the 2nd decade of life when it is only 14% [7]. Comparable results were published in a large European register [8,9]. Data from the United States [10] endorse European and Asian experiences and stress the importance of raising ADR in patients above 50 years of age.…”
Section: Factors Influencing the Adrsupporting
confidence: 48%
“…We calculated a sample size by the difference of proximal ADRs in the two groups using PASS software version 11.0 with the procedure of tests for two proportions. On the basis of a previous study, we set the proximal ADR in the EWT group at 13 % [30]. Assuming the proximal ADR in the segmental re-examination group to be 25 %, approximately 175 patients were needed in each group for a statistical power of 80 % or more and a significance level of 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Cabe resaltar que los síntomas que clínicamente sugieren con mayor fuerza la presencia de CCR son sangrado rectal y pérdida de peso (14) , y que en términos generales, la presencia de pólipos colorrectales raramente viene acompañada de síntomas antes de progresar a CCR, excepto por algunas anormalidades ocasionales en la deposición (15) . En nuestra población se encontró mayor incidencia de adenomas en hombres, y el sexo masculino es un factor de riesgo establecido para la presencia de adenomas colorrectales (16) .…”
Section: Discussionunclassified